Correlation of Proliferating Cell Nuclear Antigen and bcl-2 Expression with Tumor Front Grading and Metastasis in Laryngeal Squamous Cell Carcinoma - Boran, C; Yildiz, L; Kandemir, B; Karagoz, F; Baris, S; Aydin, O (Veda, Slovak Academy Sciences, 2003)
This study was designed to examine the immunohistochemical expression of proliferating cell nuclear antigen (PCNA) and bcl-2 protein in 45 cases with advanced laryngeal squamous cell carcinoma who had undergone total laryngectomy with unilateral modified radical neck dissection, and the relation of this expression to some prognostic factors such as tumor front grading and neck lymph node metastases. Sections were reevaluated for routine histologic grade, tumor front grading and neck lymph node metastases, and were stained with monoclonal antibodies against PCNA and bcl-2. Significant correlation was present between the severity of PCNA expression and incidence of lymph node metastasis (p<0.05). No correlation was found between the severity of PCNA expression and tumor front grading. Bcl-2 expression did not associate with either parameters. In conclusion, PCNA is important in predicting prognosis and no association is present between the bcl-2 protein expression and prognostic factors.
Keywords: Laryngeal Carcinoma; Prognosis; Tumor Front Grading; Neck Lymph Node Metastases; Bcl-2 Protein; PCNA